2016
DOI: 10.4155/bio-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Free and Conjugated Forms of Endocrine-Disrupting Chemicals in Human Biological Fluids by Gc−MS

Abstract: This allowed its successful application to the determination of EDCs in human urine, blood and breast milk. The most frequently founded were methylparaben, ethylparaben, bisphenol A and triclosan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Several components of these personal care products (PCPs) are classified as known or suspected endocrine disruptors (EDs), i.e., compounds that are able to interfere with the endocrine function in humans and wildlife [2]. EDs are easily absorbed by the skin into the central blood circulation after dermal application, and have been detected in various concentrations in human blood, urine and breastmilk [3]. Concerns have therefore been raised whether extensive use of cosmetics and skincare products could increase the risk of hormone related cancer, for instance breast cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several components of these personal care products (PCPs) are classified as known or suspected endocrine disruptors (EDs), i.e., compounds that are able to interfere with the endocrine function in humans and wildlife [2]. EDs are easily absorbed by the skin into the central blood circulation after dermal application, and have been detected in various concentrations in human blood, urine and breastmilk [3]. Concerns have therefore been raised whether extensive use of cosmetics and skincare products could increase the risk of hormone related cancer, for instance breast cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, EtPB concentrations in breast milk from mothers from the Valencian region of Spain ranged between 0.49 and 4.05 ng/mL, which was higher than in other studies (0.6-22 ng/mL) [117]. Only a few studies reported BuPB in human breast milk samples (Table 1) [114,118].…”
Section: Parabensmentioning
confidence: 68%
“…BPA is a ubiquitous environmental toxin; it is detectable in the urine samples of most adults and children because it is primarily removed by the kidneys (Doerge et al 2010). Some reports have demonstrated that serum BPA levels are negatively correlated with annual changes in estimated glomerular filtration rates, identifying BPA as a renal damage biomarker (Azzouz et al 2016). Previous studies have also shown that injection of 25 or 50 mg/kg/day of BPA resulted in albuminuria and podocytopenia.…”
Section: Resultsmentioning
confidence: 99%